RESPONSIBILITAS PENGUSAHA DIVING DAN SNORKELING TERHADAP RISIKO WISATAWAN DI PANTAI IBOIH SABANG: KAJIAN TEORI MAQASHID SYARIAH - Annisa Rizkina; Maulana, Muhammad (JURISTA: Jurnal Hukum dan Keadilan, 2024)
This research aims to examine the responsibilities held by entrepreneurs in the diving and snorkeling industry towards the safety and experience of tourists. The research method used is a qualitative approach by conducting case studies and analyzing relevant literature. The study found that employers have an obligation to provide a safe and conducive environment for tourists who wish to participate in diving and snorkeling activities. This includes effective risk management, such as regular inspection of diving equipment, monitoring of changing weather and sea conditions, and proper training of instructors and staff involved in providing services to tourists. Furthermore, employers' legal responsibilities include the obligation to provide accurate information about the risks associated with diving and snorkeling activities, and to comply with safety and environmental protection regulations applicable in their destination. Employers must also have a well-coordinated emergency plan to deal with emergency situations or incidents that may occur during tourism activities. The implication of this study is the need for increased awareness and commitment from employers in improving safety standards and service quality in the diving and snorkeling industry.